Logistic Customer Service Innovations in the Courier-Express-Parcel Sector Forced by the COVID-19 Pandemic - The Polish Perspective - Katarzyna KOLASINSKA-MORAWSKA; Marta BRZOZOWSKA; Pawel MORAWSKI (Communications of International Proceedings, 2021)
The current socio-economic stabilization characteristic of the Western techno-world was subjected to a shock with the arrival of March 2020. The impact of the SARS-CoV-2 virus attacking the global community has caused major economic changes. Regulations issued by governments around the world resulted in the closure of schools, offices, shops, restaurants and enterprises. As a result of the sequence of events, some sectors of the economies of many countries, including Poland, slowed down. Industries and enterprises included in them slowed down or even went bankrupt. However, there were also those that benefited from the pandemic "force majeure". The rapidly increasing online shopping volume generated by the pandemic has made delivery logistics a priority. It was not enough just to have a sales site and be present on auction portals. The issue of deliveries to the customer has become a critical issue - the so-called last mile. The fate of organizations and citizens has been dependent on technology and companies operating on the logistics services market, i.e. couriers, express parcels and parcels (CEP = courier express parcel).  Logistics service providers for online stores have redefined their action plans and have agile adapted to new challenges. After more than a year, the first analyzes and summaries can be made, especially in the area of innovations introduced by enterprises from the CEP industry in the field of logistic customer service. The subject of the article is an analysis of the impact of the SARS-CoV-2 virus pandemic on the quality of services offered by enterprises from the CEP industry represented in the form of innovative solutions in the customer service process. The information source was the results of secondary exploration research, which was subjected to a critical analysis of the content, and the primary material collected using the CAWI methodology. The analysis carried out shows that there is no return to the pre-pandemic state. Long-term recovery from the crisis and getting used to virtualization in terms of communication and transaction will ensure that online shopping will continue to enjoy unflagging popularity. On the other hand, a slow but gradual return to the "new normality" may result in fiercer competition between enterprises from the CEP industry and another wave of changes on the parcel market. Therefore, the consequence of this state of affairs seems to be the organizational and technological convergence of enterprises from the CEP industry, which, in order to meet the ever-increasing requirements of customers, are forced to introduce innovative solutions adequate to customer expectations, increasing the level of customers’ service quality.
Keywords: Logistic Services; Technologies; Innovations; Last Mile; Customer Service.